2023
DOI: 10.1177/13524585231155639
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid–related tissue damage in multiple sclerosis patients with iron rim lesions

Abstract: Background: In multiple sclerosis (MS), iron rim lesions (IRLs) are associated with pronounced tissue damage, higher disease severity and have been suggested as an imaging marker of chronic active inflammation behind the blood–brain barrier indicating progression. Furthermore, chronic intrathecal compartmentalized inflammation has been suggested to be a mediator of a cerebrospinal fluid (CSF)–related tissue damage. Objective: To investigate CSF markers of intrathecal inflammation in patients with at least one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Paramagnetic rim lesions (PRLs), also known as iron rim lesions (IRLs), are thought to reflect chronic active lesions with substantial microglia/macrophage inflammation [ 97 , 98 ]. Retrospective studies of patients with MS have found that, compared with patients without PRLs, patients with least one PRL had higher disability scores, T2 lesion volume, and intrathecal IgG synthesis were higher, and lower brain volume, and patients with 4 or more PRLs had more aggressive disease, and experienced greater motor and cognitive disability at an earlier age [ 97 , 98 ]. Also, PRLs have been detected in early RRMS [ 99 ].…”
Section: Biomarkers As Indicators Of “Silent” Diseasementioning
confidence: 99%
“…Paramagnetic rim lesions (PRLs), also known as iron rim lesions (IRLs), are thought to reflect chronic active lesions with substantial microglia/macrophage inflammation [ 97 , 98 ]. Retrospective studies of patients with MS have found that, compared with patients without PRLs, patients with least one PRL had higher disability scores, T2 lesion volume, and intrathecal IgG synthesis were higher, and lower brain volume, and patients with 4 or more PRLs had more aggressive disease, and experienced greater motor and cognitive disability at an earlier age [ 97 , 98 ]. Also, PRLs have been detected in early RRMS [ 99 ].…”
Section: Biomarkers As Indicators Of “Silent” Diseasementioning
confidence: 99%